Preserving the historical value and thermal properties of renovated buildings: The case of reconstructed town houses in Kosice, Slovakia - Dušan Katunský; Jana Katunská; Erika Dolníková; Kristián Hutkai (Frontiers of Architectural Research)
The restoration of monuments is of great interest, leading to more architecturally significant designs. Many promising approaches to building design foster a symbiosis of the old and the new. The paper examines the compromises between the structural and physical properties of a historic building intended for renovation, which has already undergone several renovations. Due to the limited optimization possibilities at specific levels of the renovation project, diagnostics were used during the examination of proposals. Part of the diagnostics involves measuring thermal conditions, as well as temperatures on the internal and external surfaces of the building envelopes. The study demonstrates how the properties of the outer shell affect thermal insulation and suggests methods for architects, planners and preservationists to preserve the structural forms of the facade. The goal was to show that, despite the absence of a new thermal insulation layer on the outside of the building, the standard requirements are not violated. On the inner surface of the envelope walls, the temperature does not drop below the critical value for mould growth. Additionally, there are examples of modifications to the original details and their shape after the restoration of this building.